Prospective study comparing Xalatan® eye drops and two similar generics as to the efficacy and safety profile. Issue 4 (July 2018) - Diagourtas, Andreas; Kagelaris, Kostantinos; Oikonomakis, Kostantinos; Droulias, Andreas; Kokolakis, Nikolaos; Papaconstantinou, Dimitrios
Purpose: To evaluate the efficacy and safety between two generic prostaglandins Lataz–Xalaprost (Greece) and the corresponding original drops (Xalatan ® ). Material and methods: In this prospective randomized study, 60 patients diagnosed with open-angle glaucoma or ocular hypertension were enrolled, who had never received antiglaucoma treatment. Subjects were divided randomly into three groups (Xalatan, Lataz, and Xalaprost groups) and they were studied over 16 weeks. At each visit, the mean applanation tonometry values and tear break-up time were measured. The Ocular Surface Disease Index questionnaire was used to evaluate patient's symptoms. Results: There was a statistically significant difference (p < 0.001) in the mean values of the intraocular pressure between the baseline and the last visit (Xalatan group: from 23.11 ± 1.61 mmHg to 15.81 ± 1.22 mmHg, Lataz group: from 23.26 ± 1.33 mmHg to 15.80 ± 1.47 mmHg, and Xalaprost group: from 23.08 ± 1.45 mmHg to 16.08 ± 1.38 mmHg). Both generic eye drops showed mean percentage intraocular pressure reduction comparable to the standards of prostaglandin analogues (Xalatan: 31.57%, Lataz: 32.06%, and Xalaprost: 30.34%). Xalatan reduced the tear break-up time less, followed by Lataz and then by Xalaprost (Xalatan: from 8.5 to 8 s, Lataz: from 8.2 to 7.4 s, and Xalaprost: from 8.7 to 7.7 s). Xalatan presented the best safety profile, followed by Lataz and least was Xalaprost, according to Ocular Surface Disease Index questionnaire's results. Conclusion: No significant difference was recorded in the effectiveness of each generic prostaglandin compared to the original. Furthermore, no patient had to change medication. The differences that arose in the safety profile of the three eye drops suggest a prompt closer initial monitoring of patients who are administered generic eye drops.